High-Precision Determination of Oxygen K_{α} Transition Energy Excludes Incongruent Motion of Interstellar Oxygen - Leutenegger, M A; Kühn, S; Micke, P; Steinbrügge, R; Stierhof, J; Shah, C; Hell, N; Bissinger, M; Hirsch, M; Ballhausen, R; Lang, M; Gräfe, C; et al. (Physical review letters, 2020)
We demonstrate a widely applicable technique to absolutely calibrate the energy scale of x-ray spectra with experimentally well-known and accurately calculable transitions of highly charged ions, allowing us to measure the K-shell Rydberg spectrum of molecular O_{2} with 8 meV uncertainty. We reveal a systematic ∼450  meV shift from previous literature values, and settle an extraordinary discrepancy between astrophysical and laboratory measurements of neutral atomic oxygen, the latter being calibrated against the aforementioned O_{2} literature values. Because of the widespread use of such, now deprecated, references, our method impacts on many branches of x-ray absorption spectroscopy. Moreover, it potentially reduces absolute uncertainties there to below the meV level.